Effect of a π-linker of push–pull D–π–A donor molecules on the performance of organic photodetectors. Issue 32 (15th July 2020) - Lim, Hong Chul; Choi, Min-Soo; Chae, Sangmin; Kim, Hyo Jung; Kim, Jang-Joo; Hong, Jong-In
Abstract : The BHJ OPDs based on H3 donor molecule with amorphous morphology exhibited high external quantum efficiency of 64% at 530 nm, a low J d value of 1.8 × 10 −8, and a high J ph value of 9.6 × 10 −3 A cm −2 at −3 V bias. Abstract : We report organic photodetectors (OPDs) exhibiting high photocurrent density ( J ph ), low dark current density ( J d ), and broadband external quantum efficiency (EQE) based on three push–pull type D–π–A small molecule donors (H1, H2, and H3 ) with different π-linker structures. Among the three donor molecules, H2 with a long π-linker had stronger intermolecular interactions and formed a polycrystalline structure, thus generating subgap states and trap sites at the interface, which increased the J d value of OPDs because of the facilitated electron injection from the indium tin oxide electrode to the donor at reverse bias and decreased the J ph value. In contrast, H3 with a short π-linker showed amorphous morphology in thin films because of weaker intermolecular interactions, lowering the J d value in both planar heterojunction (PHJ) OPDs and bulk heterojunction (BHJ) OPDs. The BHJ OPDs with H3 exhibited a broadband EQE value of 64% at 530 nm, a low J d value of 1.8 × 10 −8, and a high J ph value of 9.6 × 10 −3 A cm −2 at −3 V bias.